Identification of novel inhibitors of the transcriptional coactivator MRTF-A for HCC therapy - Franz, Miriam; Wenisch, Pia; Wohlleben, Petra; Rupprecht, Laura; Chubanov, Vladimir; Gudermann, Thomas; Kyheröinen, Salla; Vartiainen, Maria Kristina; Heinrich, Markus; Mühlich, Susanne (Molecular Therapy Oncology, 2024)
Myocardin-related transcription factor A (MRTF-A) is a coactivator of serum response factor (SRF), which regulates the expression of genes involved in cell proliferation, migration, and differentiation and has been implicated in hepatocellular carcinoma (HCC) progression. We recently established inhibition of the transcriptional activity of MRTF-A by NS8593 as a novel therapeutic approach for HCC therapy. NS8593 is a negative gating modulator of the transient receptor potential cation channel TRPM7. In this report, we identify an aminobenzimidazole that is highly potent in inhibiting TRPM7 and its interaction with RhoA, leading to decreased SRF transcriptional activity and enhanced nuclear export of MRTF-A, as determined by fluorescence loss in photobleaching (FLIP). This resulted in reduced expression of the MRTF/SRF target genes transforming growth factor β1 (TGF-β1) and tetraspanin 5 (TSPAN5), senescence induction, and growth arrest in HCC cells. Replacement of the tetraline core by a 3-aminophenyl substructure yielded inhibitor 10 with higher potency than inhibitor 5, and further structural modifications yielded highly potent inhibitors of SRF activity, 14 and 16. Both compounds were capable of inhibiting cell proliferation and inducing senescence in HCC cells with improved efficacy compared to NS8593. These inhibitors represent valuable tools for understanding the molecular basis of drug development targeting TRPM7 and MRTFs.
CRIS-Team Scopus Importer:2024-11-08
Keywords: HCC; MKL1; MRTF; MT: Regular Issue; NS8593; RhoA; SK; SRF; TGF-ß1; TRPM7; TSPAN5

LPA receptor 1 (LPAR1) is a novel interaction partner of Filamin A that promotes Filamin A phosphorylation, MRTF-A transcriptional activity and oncogene-induced senescence - Konopa, Andreas; Meier, Melanie; Franz, Miriam; Bernardinelli, Emanuele; Vögele, Anna-Lena; Atreya, Raja; Ribback, Silvia; Roessler, Stephanie; Aigner, Achim; Singer, Kerstin; Singer, Stephan; Sarikas, Antonio; et al. (Oncogenesis, 2022)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF), which controls fundamental biological processes such as cell growth, migration, and differentiation. MRTF and SRF transcriptional activity play an important role in hepatocellular carcinoma (HCC) growth, which represents the second leading cause of cancer-related mortality in humans worldwide. We, therefore, searched for druggable targets in HCC that regulate MRTF/SRF transcriptional activity and can be exploited therapeutically for HCC therapy. We identified the G protein-coupled lysophosphatidic acid receptor 1 (LPAR1) as a novel interaction partner of MRTF-A and Filamin A (FLNA) using fluorescence resonance energy transfer-(FRET) and proximity ligation assay (PLA) in vitro in HCC cells and in vivo in organoids. We found that LPAR1 promotes FLNA phosphorylation at S2152 which enhances the complex formation of FLNA and MRTF-A, actin polymerization, and MRTF transcriptional activity. Pharmacological blockade or depletion of LPAR1 prevents FLNA phosphorylation and complex formation with MRTF-A, resulting in reduced MRTF/SRF target gene expression and oncogene-induced senescence. Thus, inhibition of the LPAR1-FLNA-MRTF-A interaction represents a promising strategy for HCC therapy.
CRIS-Team WoS Importer:2023-01-13

Tetraspanin 5 (Tspan5), a novel gatekeeper of the tumor suppressor dlc1 and myocardin-related transcription factors (mrtfs), controls hcc growth and senescence - Schreyer, Laura; Mittermeier, Constanze; Franz, Miriam; Meier, Melanie; Martin, Dietmar E.; Maier, Kerstin C.; Hübner, Kerstin; Schneider-Stock, Regine; Singer, Stephan; Holzer, Kerstin; Fischer, Dagmar; Ribback, Silvia; et al. (Cancers, 2021)
Human hepatocellular carcinoma (HCC) is among the most lethal and common cancers in the human population, and new molecular targets for therapeutic intervention are urgently needed. Deleted in liver cancer 1 (DLC1) was originally identified as a tumor suppressor gene in human HCC. DLC1 is a Rho-GTPase-activating protein (RhoGAP) which accelerates the return of RhoGTPases to an inactive state. We recently described that the restoration of DLC1 expression induces cellular senescence. However, this principle is not amenable to direct therapeutic targeting. We therefore performed gene expression profiling for HepG2 cells depleted of DLC1 to identify druggable gene targets mediating the effects of DLC1 on senescence induction. This approach revealed that versican (VCAN), tetraspanin 5 (TSPAN5) and N-cadherin (CDH2) were strongly upregulated upon DLC1 depletion in HCC cells, but only TSPAN5 affected the proliferation of HCC cells and human HCC. The depletion of TSPAN5 induced oncogene-induced senescence (OIS), mediated by the p16INK4a/pRb pathways. Mechanistically, silencing TSPAN5 reduced actin polymerization and thereby myocardin-related transcription factor A-filamin A (MRTF-A-FLNA) complex formation, resulting in decreased expression of MRTF/SRF-dependent target genes and senescence induction in vitro and in vivo. Our results identify TSPAN5 as a novel druggable target for HCC.
CRIS-Team Scopus Importer:2021-11-05
Keywords: DLC1; MKL1; MRTF; SRF; TSPAN5